AKMEOLOGIYALÍQ QATNAS TIYKARÍNDA BOLAJAQ OQÍTÍWSHÍLARDÍŃ FUNKCIONALLÍQ KOMPETENCIYASÍN RAWAJLANDÍRÍW - Kunnazarova, B. (SCIENCE and SOCIETY, 2025)
This article analyzes the concept of functional competence, which includes knowledge, skills, and personal qualities necessary for successful pedagogical activity. In particular, the importance of the acmeological approach in shaping not only professional knowledge and skills, but also personal qualities necessary for the effective functioning of a teacher in the context of the modern educational environment is emphasized.